Investigating operational excellence in oil and gas upstream activities - Zakaria, Hasan Mohammed (2025)
The upstream oil and gas industry operates in a highly complex and volatile environment, facing challenges such as fluctuating oil prices, stringent regulations, and rising environmental and operational risks. These challenges necessitate strategic management of operational performance to ensure long-term sustainability and competitiveness. This study examines a key player company in the industry, focusing on critical performance determinants, including resource optimization, efficiency, and competitiveness. Guided by four research questions, this study explores performance management practices, the role of human resource strategies, the impact of health, safety, and environmental (HSE) protocols, and the effect of technology adoption. A qualitative research approach was employed, using semi-structured interviews with 10 key respondents, thematic analysis, framed within the Resource-Based View, Human Capital Theory, Risk Management Theory, and Socio-Technical Systems Theory. Findings highlight that cost, quality, delivery, and flexibility are key dimensions of operational performance. Effective human resource strategies enhance employee engagement and adaptability, while HSE protocols mitigate risks and improve workforce morale. Furthermore, technological advancements such as automation, the Internet of Things (IoT), and artificial intelligence (AI) significantly enhance efficiency and resilience. The primary contribution of this study is the development of a tailored operational performance management framework, integrating strategic insights with practical recommendations. This framework provides the company with a roadmap to enhance efficiency and sustain a competitive edge. Broader industry implications emphasize the importance of aligning operational strategies with performance metrics to navigate industry complexities effectively. This research offers valuable insights for oil and gas firms striving to enhance operational effectiveness in an evolving market landscape.